HIPPOCRATES IS CARE: HISTORY AND SOME BIOLOGICAL PATHWAYS ON CAREGIVER - Kalil, Rosangela Souza; Ferry, Fernando Raphael de Almeida; Sion, Fernando Samuel; Cunha-Pinto, Jorge Francisco da; Costa-Velho, Marcelo Mendes de Azevedo; Morais de Sá, Carlos Alberto (Revista de Pesquisa Cuidado é Fundamental Online, 2011)
Abstract Hippocrates is the mainstay of care. Plato and Aristotle state humoralism as the way that Hippocrates understands human health disorders. He closely observed patients to restore humoral equilibrium, relying on healing power of nature to recover health, rejecting drugs or any kind of procedure that could harm the individual. The development of a common ground of understanding is desirable as a process of negotiating treatment goals and methods which may create an atmosphere of support and solidarity. The concept of supportive care was formalized in Belgium in 1992 with attention to multicultural aspect of our population. The biological basis on care are backed on cortical circuitries, association of pathways, existence of several neurotransmitters, which mediates integrative process promoting behavior, emotion and cognitive. Care may influence favorably all these biological systems and help to improve quality of live or even cure the patient. Descriptors: Hippocrates is Care, Biological Basis on Care, Pathways of Care.